Significance of Holographic Technology in Modern World - Ghosh, A (International Journal of Computer Sciences and Engineering, 2025)
Holography projection is the new kind of technology that will change the traditional system of communication in near future. With this technology virtual images of real objects can be projected anywhere with accurate details and depth impression. This paper puts focus on holography projection technology. It also focuses on the importance of this technology, the process of construction of holograms and application features that will affect on several areas such as marketing, telecommunication, education and healthcare. It also puts light on future that will help to redesign many fields of life including businesses and technologies.